Blind spots and KGB traces in Ivanauskas’ legacy - Vilkelytė, Daiva (Genocidas ir rezistencija, 2020)
The article examines a gradual involvement in Soviet propaganda by Lithuanian biologist Tadas Ivanauskas, while simultaneously advancing his academic career in the universities of Kaunas and Vilnius after the Soviet occupation in 1940.This engagement culminated in September 1948, when a special session dedicated to examining the situation in Lithuanian biology was hosted by the Lithuanian Academy of Sciences. During this session, Prof. Ivanauskas, a Soviet academic and the head of the Institute of Biology, pronounced genetics as a false science and condemned the genetic research. In his speech, he labelled the achievements of such renowned global authorities in biology like Gregor Mendel, Thomas Hunt Morgan and August Weisman as “reactionary”, as “fake” and “metaphysically idealistic”.In his report, Prof. Ivanauskas stated that their teaching on hereditary traits in organisms did not acknowledge a possibility of changing the essence of organisms by changing their environment that would be passed on to later generations, that was established by the Soviet biologists, i.e. to “educate” the living species by changing their life circumstances.On the contrary, he said, the outstanding Soviet science had determined that new life forms could be created at will by merely changing the habitat of organisms and that these acquired changes would be passed onto next generations. All this was outlined in the works of a prominent Soviet academician Trofim Lysenko and his predecessor, a selftaught Russian botanist Ivan Michurin.“Lysenkoism”, a soviet biology pseudoscience based on a Lysenko’s personality cult of personality was introduced at the above-mentioned session. Lysenko was an influential self-taught agronomist and a pet-scientist of Joseph Stalin, but his pseudo-teachings survived after Stalin’s death. Lysenko’s pseudoscience after 1948 session replaced genetics for the upcoming 15 years in Lithuania.Biologists involved in genetic research were forced to publicly denounce their scientific “blunders”. Those who wished to continue their work in the research institutes belonging to the Soviet Lithuanian Academy of Sciences had to accept Lysenko’s doctrine. Others were fired.The article examines Ivanauskas’s legacy, albeit many documents related to his personal and professional life were destroyed after Stalin’s death. A fake persona was created and propagated, adapting to the Soviet fashions, and carefully choreographed propaganda folklore.This artificial image, a myth crafted in the era of Soviet censorship is surprisingly long-lasting. Deconstruction of this myth comes as a shock to former Ivanauskas’ students, who have graduated and matured as academicians and professors in the uncritical thinking void of the Soviet times.It was impossible to unearth enough documents to portray a fully-fledged picture of an ideologically obedient nomenclaturist. However, the article probes into the personality of a professor who served as a Lithuanian adopted version of Michurin in the backdrop of KGB arrests and academic demotions of his subordinates and co-workers.Despite a complex family life and humble scientific achievements, Ivanauskas was “promoted” to a position of a doctor in biology without writing his PhD thesis. This was made possible by a decree of the Soviet Minister of Education Antanas Venclova who “appointed” Ivanauskas to a position of a “doctor” in biology.Furthermore, a political tandem of the Head of the Supreme Soviet of the Lithuanian SSR Mečislovas Gedvilas and the Secretary of the Lithuanian Communist Party Antanas Sniečkus, the personalities with only sophomore-level education at the top of the combined legislative and executive power, appointed him to a position of an academician.All this was possible because the academic independence of university and science was annulled and made subordinate to the Communist Party’s doctrine. Scientists, who looked like potential rebels, were exiled to Siberia, their publications were banned and destroyed.Today false scientific theories, propagated by Prof. Ivanauskas are forgotten or disregarded, Ivanauskas’s undeserved academic achievements are celebrated as true. His lectures on Darwinism, lagging the global scientific discoveries in biology by some 100 years, as well as his compilations Polish and German ornithologists, were extremely popular in Soviet Lithuania. The eco of this popularity lives on.Lithuanian historians have already evaluated the damage of Lysenkoism to science and students of the country: “research carried out in the inter-war period in several branches of biology related to genetics was discontinued. Scientists who were involved in the research corresponding to the scientific level of the time had to abandon their work and to denounce it as erroneous. Along with the isolation from the global scientific development, it resulted in backwardness of the science and its disconnection from the reality of life”.While promoting the Communist Party’s propaganda camouflaged as science from his nomenclature position and justified by the undeserved scientific regalia, Prof. Ivanauskas has earned a place on par to other disgraced soviet scientists who propagated scientific communism, scientific atheism, and counterfeit history of Lithuania – Juozas Žiugžda and Mira Bordonaitė.
Keywords: Soviet Lithuania; history of science; collaborators; soviet science; communist indoctrination; Tadas Ivanauskas